Sensitivity of Echinochloa crus‐galli populations to maize herbicides: a comparison between cropping systems. (20th May 2015) - Claerhout, S; Reheul, D; De Cauwer, B; Kudsk, Per
Summary Echinochloa crus‐galli is an important maize weed with significant variation in herbicide sensitivity. This differential response may reflect differences in selection pressure caused by years of cropping system‐related herbicide usage. The herbicide sensitivity of E. crus‐galli populations from three divergent cropping systems was evaluated in dose–response pot experiments. Populations were collected from sandy fields with (i) a long‐term organic cropping system, (ii) a conventional cropping system with maize in the crop rotation or (iii) a conventional cropping system with long‐term monocropping of maize. Each cropping system was represented by six E. crus‐galli populations. The effectiveness of three foliar‐applied maize herbicides (nicosulfuron, cycloxydim and topramezone) and two soil‐applied maize herbicides (S‐metolachlor and dimethenamid‐P) was tested at three doses and two runs. Foliar‐applied herbicides were applied at the three true leaves stage. Soil‐applied herbicides were applied immediately after sowing. The foliage dry weight per pot was determined 4 weeks after treatment. Plant responses were expressed as biomass reduction. Herbicide sensitivity was consistently lowest for populations from maize monocropping systems. Compared with populations from organic cropping systems, populations from monocropping systems showed 6.9%, 9.8% and 29.3% lower sensitivity to cycloxydim, topramezone and nicosulfuron respectively. Populations from the conventional crop rotation system showed intermediate sensitivity levels, which did not significantly differ from sensitivity levels of populations from the other cropping systems. Sensitivity to dimethenamid‐P and S‐metolachlor was not affected by cropping system. Environmental conditions influenced herbicidal response. This study indicated that integrated weed management may be necessary to preserve herbicide efficacy over the long term.